A long-term (2002 to 2017) record of closed-path and open-path eddy covariance CO2 net ecosystem exchange fluxes from the Siberian Arctic. - Holl, David; Wille, Christian; Sachs, Torsten; Schreiber, Peter; Runkle, Benjamin R K; Beckebanze, Lutz; Langer, Moritz; Boike, Julia; Pfeiffer, Eva-Maria; Fedorova, Irina; Bolshiyanov, Dimitry Yu; Grigoriev, Mikhail N; et al. (PANGAEA, 2018)
Ground-based observations of atmospheric variables are necessary to progressively improve global climate models. Observed data can be used for model evaluation and to develop or tune process models. In arctic permafrost regions, climate-carbon feedbacks might potentially be intense. Therefore, increased efforts to better represent these regions in global climate models have been made in recent years. We present a multiannual time series of soil-atmosphere carbon dioxide fluxes measured in situ with the eddy covariance technique in the Siberian Arctic (72° 22' N, 126° 30' E). The site is part of the international network of carbon dioxide flux observation stations (FLUXNET, Site ID: Ru-Sam). The data set includes consistently processed fluxes based on concentration measurements of closed path and open path gas analyzers. With parallel records from both sensor types, we were able to apply a site-specific correction to open path fluxes. This correction is necessary due to a deterioration of data, caused by heat generated by the electronics of open path gas analyzers. Parameterizing this correction for subperiods of distinct sensor setups yielded good agreement between open and closed path fluxes. We compiled a long-term (2002 to 2017) carbon dioxide flux time series that we additionally gap-filled with a standardized approach.
A long-term (2002 to 2017) record of closed path and open path eddy covariance CO₂ net ecosystem exchange fluxes from the Siberian Arctic
Keywords: Carbon dioxide flux; Carbon dioxide flux, closed path; Carbon dioxide flux, closed path, quality classes; Carbon dioxide flux, open path; Carbon dioxide flux, open path, quality classes; Carbon dioxide flux, quality classes; Carbon dioxide flux, standard deviation; Eddy covariance footprint, contribution of surface class; Ru-Sam; Siberian Arctic